The effect of profitability and capital structure against company value with dividend policy as moderator variable in consumption companies registered on the 2014-2018 IDX (Research, Society and Development, 2020)
This research aimed to analyze the effect of profitability and capital structure on the Company value with Dividend policy as a moderating variable in consumption companies which registered on the Indonesia Stock Exchange for the 2014-2018 Period. The sample in this research is Consumption Company with food and drink subsector, cigarette, pharmacy, cosmetics, household goods and household appliances. The data collection technique used Purposive Sampling, so it is obtained 15 companies with 5 years of observations to 75 observations. Data analysis tools used SmartPLS 3.0. The analysis results shows that profitability has positive and significant effect on the company value, modal structure has positive and significant effect on the company value, and dividend policy is unable to moderate the effect of capital structure on the company value. The profitability and capital structure can explains the company value of 85,6% while the rest is 14,4% explains by the other variables. The analysis prove that a well-managed capital structure will increase the company's profitability and value, so the capital gains are greater and investors expect capital gains rather than dividends.